A Professional and His Work: Is Human Capital Important in Contemporary Russia? - Dmitri Popov (Journal of Economic Sociology, 1970)
This publication is a review of (and a reflection on) the recent book “Human Capital of Russian Professionals: Current State, Dynamics, Factors” published by the Russian Academy of Sciences. Over the past two decades, research has repeatedly shown that the value of human capital (at least in developed Western countries) has exceeded the value of physical capital, and it is human capital that largely determines modern economic development. Therefore, interest in human capital remains at a consistently high level, especially with regard to the research and assessment of its macroeconomic effects. At the same time, the original theory that appeared in the 1950s-60s within the Chicago school of economics defined human capital at the micro- economic level as the result of a person’s investments in his own life and his own development. The authors of the book under review attempt to comprehend sociologically human capital, revealing that behind the rather abstract idea of capital there are specific social actors—people and social groups. This perspective aligns the idea of human capital more closely with its original interpretation. The authors of the book raise the question about the significance of professionalism and, more generally, human capital (primarily knowledge, abilities, skills) within the social system of modem Russia, exploring whether they give advantages to their “bearers.” Despite its apparent obviousness and simplicity, this question turns out to be remarkably complex. The observed advantages for holders of extensive professional knowledge and skills in the post-Fordist knowledge-intensive economies (expressed in social dynamics, income, social prestige) may not be readily available to professionals in Russia. One of the pessimistic conclusions of the book is that Russian society is “stuck” somewhere in the transition to a postmodern economy and the inevitability of this transition seems to be less evident today. Apparently, professionalism and human capital play a different role in modem Russia in comparison with Western economies, which forces us to look differently at issues of dynamics, structure and social development.